Analysis of catastrophic failure of axial fan blades exposed to high relative humidity and saline environment. (August 2015) - Vargas, Javier A.; Wilches, José E.; Gómez, Humberto A.; Pacheco, Jovanny A.; Hernandez, Roque J.
Highlights: The integration of different analysis and techniques to determine the failure causes. The influence of the high relative humidity and saline environment in these systems. Increasing the knowledge for axial fan failures analysis. Abstract: One blade of an axial fan that uses air from a marine atmosphere of high relative humidity for cooling a gas turbine failed, with catastrophic consequences for the system, the fracture type is brittle. Root cause analysis of the failure involved the application of non-destructive testing, chemical and mechanical characterization of the material of the blade, the fractographic analysis of fracture surfaces, the finite element modeling of the stress condition of the blade, the use of metallographic techniques for the identification of the manufacturing process of the component, and the nature of the interaction of the structural components of the blade with the surrounding environment. It was found that: (1) the alloy of the blade corresponds to Al-2024 without heat treatment, manufactured by directional solidification; (2) the fracture mechanism is low-cycle fatigue or high tensile stress, the initiation is in a inaccessible area and covered with corrosion products originated by a process of intergranular cracking of the alloy, as a consequence of saline products deposition from the marine atmosphere in the zone.